2009
DOI: 10.1111/j.1365-2869.2008.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Error correction maintains post‐error adjustments after one night of total sleep deprivation

Abstract: SUMMAR Y Previous behavioral and electrophysiologic evidence indicates that one night of total sleep deprivation (TSD) impairs error monitoring, including error detection, error correction, and posterror adjustments (PEAs). This study examined the hypothesis that error correction, manifesting as an overtly expressed self-generated performance feedback to errors, can effectively prevent TSD-induced impairment in the PEAs. Sixteen healthy right-handed adults (seven women and nine men) aged 19-23 years were instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
(73 reference statements)
0
14
0
Order By: Relevance
“…Failures to respond, or non-responses (sometimes called errors of omission), have been noted to increase during sleep deprivation on a variety of tasks: serial subtraction 1, psychomotor vigilance 2, arrow flanker 3, semantic judgment 4, as well as working memory tasks 5-8. Understanding such failures to respond would seem to provide much insight into the disproportionate number of real-world accidents that have been attributed in part or in whole to sleep deprivation 9.…”
Section: Introductionmentioning
confidence: 99%
“…Failures to respond, or non-responses (sometimes called errors of omission), have been noted to increase during sleep deprivation on a variety of tasks: serial subtraction 1, psychomotor vigilance 2, arrow flanker 3, semantic judgment 4, as well as working memory tasks 5-8. Understanding such failures to respond would seem to provide much insight into the disproportionate number of real-world accidents that have been attributed in part or in whole to sleep deprivation 9.…”
Section: Introductionmentioning
confidence: 99%
“…The five subscales were calculated for normal state and fatigue state. In addition, the paired t-test was used to analyze the two different states (Hsieh et al, 2010;Murphy et al, 2010). Descriptive statistics of error rate, RTs of error and correct trials, and the total number of errors in fatigue and normal states were computed.…”
Section: Discussionmentioning
confidence: 99%
“…The error rate is defined as the number of error keystrokes divided by the total number of keystrokes. Error and omission rates were examined for fatigue and normal states by the paired t-test (Hsieh et al, 2010;Murphy et al, 2010). The RTs of error and correct trials were examined by repeated-measures ANOVA with the state (fatigue vs. normal, 2), trial type (correct vs. error, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Tulek et al used the Flanker task to disclose partially impaired attentional control in patients with OSA; however, their post-error analysis yielded nonsignificant results, and corrective behavior was not assessed [ 25 ]. Using the Flanker task, an experimental study on sleep deprivation revealed that post-error adjustments were maintained after one night of complete sleep deprivation [ 26 ]. In another similar study conducted by Renn et al, Flanker task results revealed mild impairment in error monitoring behavior [ 27 ].…”
Section: Discussionmentioning
confidence: 99%